PENERAPAN MEDIA PERMAINAN “SNAKES LADDERS” DALAM PEMBELAJARAN KOSAKATA BAHASA ARAB PADA KUTTAB DARUSSUNNAH PURWAKARTA - Luthfi, Taufik; Somalia, Lia; Randi, Hanina (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
Arabic learning in Kuttab Darussunnah has become part of the curriculum in the learning process, but not a few obstacles felt by a teacher in delivering learning materials, including learning Mufrodat or Arabic Vocabulary. The lack of enthusiasm in students or students in learning Arabic is one of the reasons for research to conduct research in Kuttab Darussunah. When looking at the innovation of the learning process carried out by teachers by integrating the Snakes Ladder game media (Snakes and ladders), there are several differences in the enthusiasm of students or students in participating in Arabic learning with Mufrodat Material. The method used in this is Descriptive Quantitative. And the purpose of this study is to test the accuracy of the snake and ladder method in Arabic language learning, the data in this study was obtained from observations. The results of observations state that the snake and ladder method is very appropriate to be used in the process of learning Arabic, especially in Arabic vocabulary material. In addition to improving student learning outcomes, it can also create a more pleasant and lively learning atmosphere and students are more responsive to Arabic language learning, so that students can be more active and understand more about the material taught, besides students, teachers also feel the positive impact that teachers are easier to deliver material and teachers do not feel confused by a more active atmosphere.